Pemanfaatan Teknologi Digital Untuk Meningkatkan Pembelajaran Dan Keaktifan Di Smk Negeri 1 Simpang Empat - Adi Saputra, Riski; Aprianti, Ria; Hadani, Hadani; Aslamiah, Aslamiah; Amelia, Rizky (JURNAL MANAJEMEN PENDIDIKAN, 2025)
UTILIZATION OF DIGITAL TECHNOLOGY TO IMPROVE LEARNING AND STUDENT ENGAGEMENT AT SMK NEGERI 1 SIMPANG EMPATThe integration of digital technology within the Merdeka Belajar policy has become an essential component in enhancing the effectiveness and interactivity of learning, particularly in vocational education. In the context of vocational high schools (SMK), the use of technology not only supports visual presentation of material but also strengthens student engagement in the learning process. This study aims to analyze the implementation of digital technology and its contribution to learning effectiveness and student activeness at SMK Negeri 1 Simpang Empat, Banjar Regency. This research employs a descriptive qualitative approach involving the principal, productive and normative subject teachers, as well as students. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and verification of findings. The results show that digital technologies such as Interactive Flat Panel (IFP), Google Classroom, and interactive digital media have been utilized in learning with varying levels of intensity across subjects. The use of IFP supports the visualization of practical procedures, while digital platforms facilitate task management, communication, and feedback. The use of technology has been proven to improve learning effectiveness by providing more flexible access to materials and clearer instructional delivery. Student activeness also increases through digital discussions, collaboration, and more responsive participation in learning activities. Challenges encountered include unstable internet connectivity, variation in digital literacy skills, and limited access to devices among students. The study concludes that digital technology contributes positively to learning effectiveness and student activeness. Further optimization requires strengthening teachers’ digital pedagogical competence, improving network infrastructure, and providing student support to enhance digital literacy.